Effect of Metformin on Myocardial Injury Induced by Hepatic Ischemia-Reperfusion in Rats - An, Wen; Kang, Ju-Seop (Frontiers in Pharmacology, 2022)
Background: There is no effective medication for treatment or prevention of hepatic ischemia-reperfusion (HIR) injury caused by liver transplantation and hepatectomy. This study aimed to investigate the therapeutic effects of metformin on HIR injury and related myocardial injury in rats. Methods: Wistar male rats were randomly divided into three groups: sham group, ischemia-reperfusion group, and IR group treated with metformin 150 mg/kg. Wistar male rats were administered metformin (150 mg/kg) or saline 30 min pre-operative and underwent 15 min ischemia and 6 h reperfusion (n=4). Results: Metformin significantly alleviates the injury caused by HIR. Administration of metformin resulted in a significant reduction in the serum levels of alanine transaminase and aspartate transaminase and the activity of malondialdehyde, creatine kinase MB, and lactate dehydrogenase but maintained high catalase and superoxide dismutase activity. Metformin significantly inhibited the IR-induced elevation of tumor necrosis factor-α in liver and heart tissue. Conclusion: Metformin can alleviate hepatic and myocardial injury induced by IR by inhibiting oxidative stress.